2007
DOI: 10.1128/aac.01448-06
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Fosmidomycin-Clindamycin versus Sulfadoxine-Pyrimethamine in the Treatment of Plasmodium falciparum Malaria

Abstract: Fosmidomycin-clindamycin therapy given every 12 h for 3 days was compared with a standard single oral dose of sulfadoxine-pyrimethamine. The two treatments showed comparably good tolerabilities and had an identical high degree of efficacy of 94% in a randomized trial carried out with 105 Gabonese children aged 3 to 14 years with uncomplicated malaria. These antimalarials merit further clinical exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
(21 reference statements)
0
40
1
1
Order By: Relevance
“…Furthermore, in vitro synergistic activity between fosmidomycin and clindamycin against various strains of P. falciparum has been demonstrated (27). Different clinical trials have confirmed the safety and efficacy of fosmidomycin alone (15) or combined with clindamycin for the treatment of uncomplicated P. falciparum both in adults (17,18,20,23) and in older children (3,5,6,20). However, data on the efficacy of this combination in younger children, the age group most affected by malaria worldwide, are scarce.…”
mentioning
confidence: 99%
“…Furthermore, in vitro synergistic activity between fosmidomycin and clindamycin against various strains of P. falciparum has been demonstrated (27). Different clinical trials have confirmed the safety and efficacy of fosmidomycin alone (15) or combined with clindamycin for the treatment of uncomplicated P. falciparum both in adults (17,18,20,23) and in older children (3,5,6,20). However, data on the efficacy of this combination in younger children, the age group most affected by malaria worldwide, are scarce.…”
mentioning
confidence: 99%
“…11 A number of clinical studies have demonstrated that fosmidomycin in combination with clindamycin has efficacy and good tolerability in the treatment of P. falciparum malaria. [17][18][19] In 2005, Dhiman et al 20 showed that fosmidomycin inhibits M. tuberculosis DXR (MtDXR) with an IC 50 of 0.31 µM, but has no effect on M. tuberculosis cell growth. The antibacterial activity of fosmidomycin on E. coli has been shown to rely on a cAMP-dependent glycerol-3-phosphate transporter that allows uptake in that organism, 21 but which seems to be lacking in M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fosmidomycin is used widely as a DXR inhibitor. In a clinical study, fosmidomycin-clindamycin was found to be efficient in the treatment of 105 Gabonese patients representing children aged 3 to 14 years with uncomplicated malaria, demonstrating its application in clinical trials (19). Moreover, eleven mixes with expansive basic assorted qualities were tried against Toxoplasma gondii DXR and a few strong inhibitors were identified with very low 48 nM Ki values (29).…”
Section: Discussionmentioning
confidence: 99%
“…1-Deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) is the second enzyme of the pathway, catalysing the reduction and isomerization of 1-deoxy-D-xylulose-5-phosphate (DXP) to 2-Cmethyl-D-erythritol-4-phosphate (MEP) by utilizing Mg2+ and NADPH as enzyme cofactors. Potential inhibitor, fosmidomycin, a naturally occurring antibiotic against DXR, has already been identified and has demonstrated antimalarial activities in preclinical studies and clinical tribulations (17)(18)(19). These findings insinuate that DXR is a valid target, and inhibitors of this enzyme could serve as potential guides for apicomplexan's chemotherapy.…”
Section: Introductionmentioning
confidence: 99%